2017
DOI: 10.18805/ijar.b-3268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peripartum nutritional supplementation on postpartum fertility and blood biochemical and steroid hormone profile in crossbred cows

Abstract: Advanced pregnant healthy HF crossbred cows (n=20) of 2-4 parity were equally divided in to control (routine farm feeding-RFF) and treatment/nutrients supplementation (RFF + bypass fat @ 100-200 g/h/d and ASMM @ 50 g/h/d) groups and were studied from 2 wks prepartum to 8 wks postpartum for plasma profile of steroid hormones and metabolites on days -14, -3, 0, +3, +14, +28 and +42 as well as for puerperal events and postpartum fertility. The mean plasma progesterone values were maximum (>6 ng/ml) on day 14 prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 22 publications
(34 reference statements)
19
15
0
Order By: Relevance
“…This trend of peripartum plasma progesterone concentration corroborated well with the earlier reports in buffaloes [8-11] and cattle [3,12]. In this study, basal value of 0.2-0.8 ng/ml found on the day of calving was suggestive of complete luteolysis at parturition and corroborated with the findings of previous workers [13-16].…”
Section: Resultssupporting
confidence: 93%
“…This trend of peripartum plasma progesterone concentration corroborated well with the earlier reports in buffaloes [8-11] and cattle [3,12]. In this study, basal value of 0.2-0.8 ng/ml found on the day of calving was suggestive of complete luteolysis at parturition and corroborated with the findings of previous workers [13-16].…”
Section: Resultssupporting
confidence: 93%
“…Dietary supplementation of fat increases the circulating concentrations of cholesterol, which serves as a precursor for the synthesis of progesterone by ovarian luteal cells and also increases the lifespan of induced CL (Rahbar et al, 2014). The gradual rise in mean plasma progesterone level on day 45 and 60 postpartum in the present study is supported by the findings of previous workers (Dhami et al, 2017;Kalasariya et al, 2017), who also observed gradual rise in progesterone prior to first postpartum estrus in cattle and buffalo.…”
Section: Resultssupporting
confidence: 93%
“…The present significant decreasing trend prepartum and increasing trend postpartum of plasma progesterone concentrations observed in buffaloes during transitional period corroborated with the earlier findings of Ullah et al (2010), Ashmawy (2015) and Kalasariya et al (2017) in buffaloes and Gowda et al (2015) and Dhami et al (2017) in cattle. In the present study, the basal value of progesterone found on the day of calving was suggestive of complete luteolysis at parturition and corroborated with the findings of Momongan et al (1990) and Kalasariya et al (2017).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Female reproduction including ovary development is influenced by estrogen and progesterone hormones, the genes that regulate their production and the estrogen and progesterone receptors that mediate their action Kang et al (2012a) Naikoo et al (2016) and Dhami et al (2017). The purpose of the study was therefore, to determine the role of ICA in reproduction by assessing the reproductive index (RI), In Vitro Maturation (IVM) rates of oocytes seen as extrusion of polar body 1 (pb1), steroidogenesis of 17-estradiol (17-E 2 ) and progesterone (P 4 ), gene expression of steroidogenic (Star, Cyp19a1 and Hsd17b1) genes, important in estrogen synthesis and protein expression of estrogen receptors (ER) ,  and progesterone receptor A (PRA).…”
Section: Introductionmentioning
confidence: 99%